Stainless steels and specialty alloys for pulp, paper and biomass conversion : a practical guide for mill engineers - Garner, Andrew (Nickel Institute, 2017)
This reference book spans changes in materials of construction driven by three recent drivers: ecological clean-up, cost efficiency, and new bioeconomy products.